2010
DOI: 10.1128/iai.00435-10
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response ofLeptospira interrogansto Iron Limitation and Characterization of a PerR Homolog

Abstract: Leptospirosis is a globally significant zoonosis caused by Leptospira spp. Iron is essential for growth of most bacterial species. Since iron availability is low in the host, pathogens have evolved complex iron acquisition mechanisms to survive and establish infection. In many bacteria, expression of iron uptake and storage proteins is regulated by Fur. L. interrogans encodes four predicted Fur homologs; we have constructed a mutation in one of these, la1857. We conducted microarray analysis to identify iron-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
106
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 76 publications
11
106
2
4
Order By: Relevance
“…Detailed microarray studies of V. cholerae Fur (vcFur)-dependent gene regulation have shown that vcFur is involved predominately in the negative regulation of iron acquisition or metabolism genes (1). Similar results have been observed in Fur studies in diverse groups of bacterial pathogens (1)(2)(3)(4). In nearly all cases, expression studies have been performed during logarithmic growth and often in defined rich medium.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Detailed microarray studies of V. cholerae Fur (vcFur)-dependent gene regulation have shown that vcFur is involved predominately in the negative regulation of iron acquisition or metabolism genes (1). Similar results have been observed in Fur studies in diverse groups of bacterial pathogens (1)(2)(3)(4). In nearly all cases, expression studies have been performed during logarithmic growth and often in defined rich medium.…”
supporting
confidence: 69%
“…Expression profiles of bacteria lacking transcriptional regulators have been used successfully to broadly define genes impacted by the deleted regulator (1)(2)(3)(4). Although providing informative data, transcriptional analysis alone cannot distinguish between direct and indirect regulatory effects or identify regulated genes that may be transcriptionally silent under the test conditions.…”
mentioning
confidence: 99%
“…Interestingly, Lo et al did not observe an increase in katE expression levels within wild-type Leptospira cells under iron-limiting conditions (33), and similarly, in this study, we did not observe an increase in KatE expression levels upon the exposure of wild-type Leptospira bacteria to hydrogen peroxiderich conditions. Combined, these studies suggest that in Leptospira temperature may serve as an environmental cue resulting in altered KatE expression, which differs from the requirement for H 2 O 2 for the altered expression of ROS-detoxifying enzymes observed for Salmonella enterica serovar Typhimurium and Escherichia coli (55).…”
Section: Discussionmentioning
confidence: 33%
“…interrogans encounters diverse environmental signals at different stages of its life cycle. Studies of individual genes and whole transcriptomes and proteomes have revealed a number of L. interrogans genes that are differentially expressed when the spirochete is incubated under conditions likely to be encountered during host infection (3)(4)(5)(6)(7)(8)(9)(10)(11). Levels of specific outer membrane proteins also differ during acute infection of the liver (12) and in leptospires exiting the host in urine (13).…”
mentioning
confidence: 99%